2019
DOI: 10.20414/edulangue.v2i1.696
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Self-Regulated Strategy Development on Tertiary EFL Students' Writing Skills

Abstract: This study aimed to investigate the relative effect of Self-Regulated Strategy Development (SRSD) teaching approach on tertiary EFL students’ writing. During two months, sixty EFL University students enrolling in basic writing course took part in this project and were divided into experimental and control groups. Pre- and post-tests were carried out to garner the intended data pertinent to the students’ writing scores. A mixed-design ANOVA was carried out to analyze the changes of writing scores of the respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…They can also learn efficiently in terms that they can learn within expected time period that the teacher had set so that there is not time to waste. In this area, there are at least four domains to consider: students' group orientation, learning environment, cognitive style, and intelligent preference (Tomlinson, 2001, Rahman et al, 2019. The data from the observation showed that the group orientation, learning environment and cognitive style are influential for the flow of the learning process.…”
Section: Productmentioning
confidence: 99%
“…They can also learn efficiently in terms that they can learn within expected time period that the teacher had set so that there is not time to waste. In this area, there are at least four domains to consider: students' group orientation, learning environment, cognitive style, and intelligent preference (Tomlinson, 2001, Rahman et al, 2019. The data from the observation showed that the group orientation, learning environment and cognitive style are influential for the flow of the learning process.…”
Section: Productmentioning
confidence: 99%